The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.2147/cmar.s254630
|View full text |Cite
|
Sign up to set email alerts
|

<p>LINC01094 Down-Regulates miR-330-3p and Enhances the Expression of MSI1 to Promote the Progression of Glioma</p>

Abstract: Background: This study aims at probing into the expression, function, and mechanism of LINC01094 and miR-330-3p in glioma. Materials and Methods: qRT-PCR was employed to examine LINC01094 and miR-330-3p expressions in gliomas. After gain-of-function and loss-of-function models were constructed, CCK-8 and Transwell assays were used to detect the proliferation, migration and invasion of LN229 and U251 cells, respectively. Additionally, dual luciferase reporter gene assay was utilized to verify the binding site b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Moreover, inhibiting LINC01094 attenuated proliferation, migration and invasion of ccRCC cells (17). LINC01094 overexpression promoted the proliferation and motility of glioma cells (45). Consistent with these findings, in the present study, functional assays of LINC01094 were performed in OC cells, revealing that silencing LINC01094 inhibited OC cell viability, migration, invasion and G2/M cycle progression, and promoted OC cell apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, inhibiting LINC01094 attenuated proliferation, migration and invasion of ccRCC cells (17). LINC01094 overexpression promoted the proliferation and motility of glioma cells (45). Consistent with these findings, in the present study, functional assays of LINC01094 were performed in OC cells, revealing that silencing LINC01094 inhibited OC cell viability, migration, invasion and G2/M cycle progression, and promoted OC cell apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…MIR3142HG is a critical regulator of the inflammatory response, and the attenuated expression of MIR3142HG/miR-146a contributes to the reduced inflammatory response in IPF fibroblast ( Hadjicharalambous et al, 2018 ). As for LINC01094, several studies reported that it is a pro-tumorigenic lncRNA, and microRNA-184 ( Xu H. et al, 2020 ), miR-126-5p ( Li and Yu, 2020 ), miR-577 ( Xu J. et al, 2020 ), miR-330-3p ( Zhu et al, 2020 ), and miR-224-5p ( Jiang et al, 2020 ) were identified as its targets. The role of ABALON, AC004009-2, and LINC01711 has not been explored by biological assays, providing directions and clues for future research.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01094 can promote the development of ccRCC by upregulating SLC2A3 via miR-184 or via miR-224-5p/CHSY1 and triggers radio-resistance in ccRCC via miR-577/CHEK2/FOXM1 axis [28][29][30]. Acting as a ceRNA as well, LINC01094 promotes progression of ovarian cancer and glioma [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%